Treatment of metal plating wastewater using iron electrode by electrocoagulation process: Optimization and process performance - Oden, Muhammed Kamil; Sari-Erkan, Hanife (INST CHEMICAL ENGINEERS, 2018)
In this study, electrocoagulation (EC) process was used to remove COD, color and several toxic heavy metals from metal plating wastewater and central composite design (CCD) combined with response surface methodology (RSM) were applied for optimizing the operating parameters of the process, which utilized iron (Fe) electrodes. The interaction effects of the current density, reaction time and initial pH were analyzed and were correlated to assess the removal efficiencies for COD, color, total chromium, nickel and zinc. The ANOVA results revealed that the predicted models for the experimental design were within 95% confidence level, coefficient of determination (R-2) and adjusted R-2 were found to be higher than 96.44% and 90.04% respectively for all responses. Removal efficiencies were determined to be 76.2%, 99.9%, 98.9%, 96.3% and 99.8% for COD, color, total chromium, nickel and zinc, respectively under optimum operating conditions. In terms of electrical energy consumption and electrode consumption, the operational cost of the EC process for the removal of COD at optimum conditions was calculated to be 6.55 (sic)/m(3). The results show that the EC process seems to be an efficient treatment method for the removal of COD and toxic heavy metals from the metal plating wastewater. (C) 2018 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Metal plating wastewater; Toxic metal removal; Electrocoagulation; Iron electrode; Optimization; Response surface method; HEAVY-METALS; ARSENIC REMOVAL; ELECTROCHEMICAL TREATMENT; AQUEOUS-SOLUTIONS; FENTON PROCESS; EFFLUENT; GROUNDWATER; IONS; ALUMINUM; CU2+; Engineering